RANCANG BANGUN ALAT PENDETEKSI KELEMBABAN TANAH BERBASIS INTERNET OF THINGS - FITRIANTO, RIZKY MOHAMMAD; HARTAWAN, LIMAN (e-Proceeding FTI, 2024)
Soil moisture is important for a plant if soil moisture is lacking or excess then the growth of a plant will be disrupted. So from this, an internet of things based soil moisture detection tool was created, the purpose of this study was to produce a site and system design for soil moisture detection devices and produce programs for internet of things based soil moisture devices and obtain the physical form of internet based soil moisture devices. of things. The material used for this soil moisture detector is PVC and this tool uses a soil moisture sensor which functions as a soil moisture detector and sends commands to NodeMCU ESP8266 to turn on the relay so that the 12V selenoid valve can flow water according to soil needs and send soil moisture data to Arduino IoT Cloud application. Making this final project is done by designing, manufacturing, and procuring the components needed for this soil moisture detector. Components for the system which includes the NodeMCU ESP8266 as the controller of the relay to turn on and off the 12V solenoid valve. The solar panel functions to supply power for the system and the battery functions to store power from the solar panels and there is an ACS712 current regulator and an OV-25V voltage regulator which functions to monitor the current and voltage flowing from the solar panel to the BMS 3S 10A and then use ADS1115 for readings from analog to digital and use a buck converter MP1584 to step down. The results obtained are the physical form of the place and the system of the internet of things based soil moisture detector and produce a program for the internet of things based soil moisture detector. Abstrak Kelembaban tanah merupakan hal yang penting untuk suatu tanaman jika kelembaban tanah kurang atau berlebih maka pertumbuhan dari suatu tanaman akan terganggu. Maka dari hal tersebut dibuatlah alat pendeteksi kelembaban tanah berbasis internet of things, tujuan dari penelitian ini adalah menghasilkan rancangan tempat dan sistem untuk alat pendeteksi kelembaban tanah dan menghasilkan program untuk alat kelembaban tanah berbasis internet of things. Bahan yang digunakan untuk tempat alat pendeteksi kelembaban tanah ini adalah pvc dan alat ini mengunakan sensor kelembaban tanah yang berfungsi sebagai pendeteksi kelembaban tanah dan mengirim perintah kepada NodeMCU ESP8266 guna menghidupkan relay agar selenoid valve 12V dapat mengaliri air sesuai kebutuhan tanah dan mengirim data kelembaban tanah ke aplikasi Arduino IoT Cloud. Pembuatan tugas akhir ini dilakukan dengan merancang,membuat, dan mengadakan komponen-komponen yang dibutuhkan untuk alat pendeteksi kelembaban tanah ini. Komponen untuk sistem yang meliputi NodeMCU ESP8266 sebagai pengendali dari relay untuk menghidupkan dan mematikan selenoid valve 12V. Panel surya berfungsi untuk menyuplai daya untuk sistem dan baterai berfungsi untuk menyimpan daya dari panel surya dan terdapat regulator arus ACS712 dan regulator tegangan OV-25V yang berfungsi untuk memonitoring arus dan tegangan yang mengalir dari panel surya ke BMS 3S 10A lalu menggunakan ADS1115 untuk pembacaan dari analog ke digital dan menggunakan untuk menurunkan tegangan buck converter MP1584. Hasil yang didapatkan adalah wujud fisik tempat dan sistem dari alat pendeteksi kelembaban tanah berbasis internet of things dan menghasilkan program untuk alat pendeteksi kelembaban tanah berbasis internet of things.